Re-TaRo (Remaja Tanpa Rokok): Education on the Impact andSimulation of the Dangers of Smoking - Kania Imanuella Rante Kania Imanuella Rante; Ihza Abi Said Almi; Nabila Azizah; Rury Aulia Cantika,; Hanum Haniefa; Ega Januaryl; Rina Tri Agustini (Faculty of Public Health Mulawarman University, Indonesia, 2025)
The Field Learning Experience as known as Pelatihan Belajar Lapangan (PBL) course is part of the Faculty of Public Health curriculum, which aims to provide students with direct practical experience in the community. The village of Bukit Pariaman, where the PBL is conducted, is located in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. Based on the initial observations, one of the main health issues that was found is habit of smoking inside the house. The RE-TARO (Remaja Tanpa Rokok/Teenagers Without Cigarettes) program is an intervention effort designed to increase teenagers' awareness and understanding of the dangers of smoking in the working area of Posyandu Sejahtera 1, Bukit Pariaman Village. The RE-TARO program is held after the Teenagers Health Post activities. The target of this activity is teenagers aged 10-18 years from all areas of Bukit Pariaman Village. The activity began with an information session on the dangers of smoking, which aimed to increase adolescents' knowledge and awareness of the negative health effects of smoking. This series of activities included a pre-test, presentation of material, interactive discussion sessions, educational games, and concluded with a post-test. The activity then continued with a simulation of the dangers of smoking as a form of contextual learning. In this simulation, participants were shown an experiment illustrating the effects of smoking on the lungs using simple teaching aids. The activity concluded with a brainstorming session to explore participants' understanding of the simulation results. Through this approach, it is hoped that teenagers will be able to understand the dangers of smoking more realistically and deeply, with a target of 98% of participants being able to absorb the message conveyed through the simulation. The main objective of the RE-TARO (Teenagers Without Cigarettes) program is to increase adolescents’ knowledge and awareness about the dangers of smoking and to encourage the development of a healthy lifestyle free from cigarettes. This program is designed as an educational intervention that combines counseling, interactive discussions, educational games, and smoking hazard simulations to help participants understand the risks of smoking more clearly and deeply. Through pre-test and post-test methods, the program also aims to measure the effectiveness of improving adolescents’ understanding of smoking dangers. With a participatory and contextual approach, this program is expected to instill critical attitudes and prevent teenagers from starting to smoke, thereby supporting the creation of a smoke-free social environment and improving public health from an early age